2007
DOI: 10.1189/jlb.0906564
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte p110α phosphatidylinositol 3-kinase regulates phagocytosis, the phagocyte oxidase, and cytokine production

Abstract: Mononuclear phagocytes are critical modulators and effectors of innate and adaptive immune responses, and PI-3Ks have been shown to be multifunctional monocyte regulators. The PI-3K family includes eight catalytic isoforms, and only limited information is available about how these contribute to fine specificity in monocyte cell regulation. We examined the regulation of phagocytosis, the phagocyte oxidative burst, and LPSinduced cytokine production by human monocytic cells deficient in p110␣ PI-3K. We observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 81 publications
2
23
1
1
Order By: Relevance
“…Moreover, the kinase inhibitors alone modestly increased TNF-␣ and IL-1␤ production. Thus, our findings are in accordance with those of earlier studies showing that inhibition of the PI3K/Akt pathway increased cytokine and tissue factor expression induced by LPS treatment of murine and human macrophages (18,26,29), and activation of the PI3K/Akt pathway by insulin reduced inflammation in mice administered LPS (24). A number of mechanisms may be contributing to PI3K/Akt-mediated negative regulation of cytokine expression.…”
Section: Vol 77 2009supporting
confidence: 82%
“…Moreover, the kinase inhibitors alone modestly increased TNF-␣ and IL-1␤ production. Thus, our findings are in accordance with those of earlier studies showing that inhibition of the PI3K/Akt pathway increased cytokine and tissue factor expression induced by LPS treatment of murine and human macrophages (18,26,29), and activation of the PI3K/Akt pathway by insulin reduced inflammation in mice administered LPS (24). A number of mechanisms may be contributing to PI3K/Akt-mediated negative regulation of cytokine expression.…”
Section: Vol 77 2009supporting
confidence: 82%
“…These results are consistent with the recent reports by Lee et al (21). They demonstrated that a deficiency in PI3K p110␣ in THP-1 monocytic cells suppressed IL-12p40 protein production and mRNA expression induced by LPS (21). On the other hand, PI3K p110␣ siRNA significantly suppressed IL-12 protein production, while it had little effect on IL-12 mRNA expression in MD-DCs (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…IкB kinase regulatory subunit ERC1 is required for NFкB activation (Ducut Sigala et al 2004), and CARM1/PRMT4 has been shown to function as a promoter-specific NFкB regulator (Covic et al 2005). In monocytes and macrophages, LPS is implicated in PIK3 and AKT pathway activation (Guha and Mackman 2002;Lee et al 2007). In monocytes, a dependence of LPS-induced AKT activation on class I A of the three PIK3 classes (Cantley 2002) has been shown by RNAi-mediated PIK3CA silencing (Lee et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In monocytes and macrophages, LPS is implicated in PIK3 and AKT pathway activation (Guha and Mackman 2002;Lee et al 2007). In monocytes, a dependence of LPS-induced AKT activation on class I A of the three PIK3 classes (Cantley 2002) has been shown by RNAi-mediated PIK3CA silencing (Lee et al 2007). In contrast, RIP-Chip experiments with untreated macrophages and after LPS-activation employing an antibody against TTP revealed that TTP modulates the inflammatory response by controlling the stability of mRNAs, which encode pro-and antiinflammatory cytokines (Stoecklin et al 2008;Kratochvill et al 2011).…”
Section: Discussionmentioning
confidence: 99%